2021
DOI: 10.1186/s12886-021-02184-y
|View full text |Cite
|
Sign up to set email alerts
|

Study on the enlargement index of femtosecond laser-assisted capsulorhexis in 2–6-year-old patients with congenital cataract

Abstract: Background To identify the capsule enlargement index after femtosecond laser-assisted anterior capsulorhexis in 2–6-year-old children who underwent congenital cataract surgery. Methods In this prospective case series study, femtosecond laser-assisted anterior capsulorhexis was performed in patients with congenital cataract, aged 2–6 years. The actual achieved capsulorhexis diameters were measured with Digimizer version 4.2.6. Correlation coefficien… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 21 publications
(20 reference statements)
0
6
0
Order By: Relevance
“…Furthermore, Liao et al investigated the other factors that could affect ARCD in pediatric cataract surgery, including AL, ACD, K1 and K2. They found that AL and ACD were the most powerful influencing factors of ARCD by developing a multiple linear regression model [ 13 ]. However, as far as we know, no previous study has dealt with the development of multiple linear regression model for ARCD in the area of adult cataract surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Liao et al investigated the other factors that could affect ARCD in pediatric cataract surgery, including AL, ACD, K1 and K2. They found that AL and ACD were the most powerful influencing factors of ARCD by developing a multiple linear regression model [ 13 ]. However, as far as we know, no previous study has dealt with the development of multiple linear regression model for ARCD in the area of adult cataract surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, clinicians have often noticed that the actual resulting capsulorhexis diameter (ARCD) is different from the attempted (programmed) capsulorhexis diameter by comparing the size between optics of IOLs and capsulorhexis. In fact, previous clinical studies have demonstrated the deviation of ARCD from the programmed diameter in FLACS [ 10 13 ]. Thus, it may be useful to identify the preoperative variables that influence the ARCD.…”
Section: Introductionmentioning
confidence: 99%
“…10 Recently, a new formula was validated in 2-6-year-old patients with congenital cataract. 28 In contrast to Bochum formula, the new one does not take into account patient's age at time of surgery. Although physical measurements on the achieved capsulotomy diameters were not performed, in all cases, satisfiable results were achieved.…”
Section: Discussionmentioning
confidence: 99%
“…The anterior capsulotomy diameter programmed at the laser platform was calculated using the Bochum formula, which adjusts for age-dependent enlargements of the laser-assisted capsulotomy 10. Recently, a new formula was validated in 2–6-year-old patients with congenital cataract 28. In contrast to Bochum formula, the new one does not take into account patient’s age at time of surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the position of the IOL was more stable than the anterior capsulotomy created manually by convention; however, some surgeons have found that the actual diameter of the capsulotomy (ADC) is sometimes different from the predicted diameter of the capsulotomy (PDC), especially in children. [4][5][6][7][8] Therefore, to help clinicians to achieve the ideal CCC size, this study aimed to compare the ADC and PDC after femtosecond laser-assisted capsulotomy and identify the factors affecting the ADC in patients with cataract who underwent femtosecond laser-assisted cataract surgery (FLACS).…”
mentioning
confidence: 99%